Telehealth in India: helping to achieve health for all. (10th June 2017) - Pathak, Anubha; Kumar, Deepak
Abstract : Telecommunication technologies, such as smartphones and digital cameras, are revolutionising both animal and human healthcare through the use of telehealth. This is particularly useful in developing countries, where there may be a lack of healthcare infrastructures and an increased risk from zoonotic diseases. In this article, Anubha Pathak and Deepak Kumar discuss how telemedicine is being used in zoonotic disease research in India.